PENGOBATAN TRADISIONAL JAWA DALAM MANUSKRIP SERAT PRIMBON JAMPI JAWI - Hesti Mulyani; Sri Harti W; Venny Indria E (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2017)
AbstractThis study aims to describe Javanese traditional medical care in the Serat Primbon Jampi Jawi manuscript. It used the modern philology approach. The source of the researchdata was Serat Primbon Jampi Jawi Volume I, a collection of the Reksapustaka Library,Mangkunegaran, Surakarta. The research findings are as follows. First, Javanese traditionalmedical care is found for intestinal worms and dysentery (bloody stools). Second,the ingredients/medical prescriptions are in the form of: root (narcissus), wood/bark(sandalwood, kayu timur, and mesoyi), leaves (tamarind, lampes, and trawas), fruits (anise,chili, areca nut, and nutmeg), seeds (black cumin and coriander ), flowers (clove and apen),bulbs (garlic), and rhizomes (bengle, dlingo, and black curcuma). Other complementaryingredients are hot fresh water, salt, snakehead murrel, and starch. Third, herb/prescriptionprocessing methods include: (a) burning, (b) steaming in a rice steamer, (c) chewing, (d)smoothing, and (e) boiling. Fourth, the medical care methods include cekok (force-feeding)and sembur (spraying from the mouth for an external treatment).Keywords: traditional medical care, Javanese manuscript, cekok, sembur